Challenges and Solutions in Improving School Infrastructure in Remote Areas - Yusup, Muhammad Firdaus Bin (Journal of Strategy and Transformation in Educational Management, 2024)
Improving school infrastructure in remote areas presents numerous challenges, ranging from geographic isolation and limited accessibility to inadequate funding and resources. This article examines the multifaceted obstacles that hinder the development of educational facilities in these regions. It also explores potential solutions to overcome these challenges, including government policies, community involvement, and innovative technological approaches. By analyzing case studies and successful projects, the article highlights the importance of a collaborative effort among stakeholders to ensure sustainable and equitable educational infrastructure. The findings emphasize that addressing these challenges requires a comprehensive strategy that integrates local context and needs, promoting not only physical infrastructure improvements but also the overall quality of education. This study aims to provide a roadmap for policymakers, educators, and community leaders to enhance the learning environment in remote areas, ultimately contributing to the broader goal of educational equity and inclusion.